2007
DOI: 10.1227/01.neu.0000255447.90106.12
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of Calcium Alginate Gel as a Biocompatible Material for Endovascular Aneurysm Embolization in Vivo

Abstract: Calcium alginate was an effective endovascular occlusion material that filled the aneurysm and provided an effective template for tissue growth across the aneurysm neck after 30 days and up to 90 days. Complete filling of the aneurysm with calcium alginate ensures stability, biocompatibility, and optimal healing for up to 90 days in swine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…11 A potential explanation for these (contradictory) findings might be that acute thrombosis induces inflammation on such a large scale that it over-runs the aneurysm wall defense mechanisms or that fibrin biopolymer leads to a thicker clot than normal coagulation. Acute thrombus induction has been linked to mural destabilization not only in experimental aneurysms 22,23 but also in the clinical setting after application of flow diverters to treat intracranial aneurysms. 24,25 These studies consistently found histopathologic characteristics comparable with those found in our study, with large amounts of inflamed cells and mural cells loss in destabilized aneurysm wall segments after rapid thrombosis.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A potential explanation for these (contradictory) findings might be that acute thrombosis induces inflammation on such a large scale that it over-runs the aneurysm wall defense mechanisms or that fibrin biopolymer leads to a thicker clot than normal coagulation. Acute thrombus induction has been linked to mural destabilization not only in experimental aneurysms 22,23 but also in the clinical setting after application of flow diverters to treat intracranial aneurysms. 24,25 These studies consistently found histopathologic characteristics comparable with those found in our study, with large amounts of inflamed cells and mural cells loss in destabilized aneurysm wall segments after rapid thrombosis.…”
Section: Limitationsmentioning
confidence: 99%
“…24,25 These studies consistently found histopathologic characteristics comparable with those found in our study, with large amounts of inflamed cells and mural cells loss in destabilized aneurysm wall segments after rapid thrombosis. 22,23,25 However, the cell loss observed in healthy aneurysms could also be attributed to ischemic or inflammatory reactions induced by the fibrin polymer thrombus. It might also be possible that luminal fibrin polymer lead to a thicker clot than normal coagulation and impaired diffusion of nutrients to the healthy media and promoted inflammation as a secondary reaction.…”
Section: Limitationsmentioning
confidence: 99%
“…Lateral wall aneurysms were surgically created in the right common carotid artery of canines as previously described. 1,14,15 Prior to embolization, animals were given an intravenous bolus injection of 3000 IU heparin, followed by a maintenance injection of 500 IU every 30 minutes during the procedure to control clotting. Postoperatively, animals were placed on chronic aspirin at a dose of 81.25 mg/day.…”
Section: Surgical Aneurysm Creationmentioning
confidence: 99%
“…Because swine generally have heightened healing responses to embolization, 1,11,20,34,35 in the present study we investigated the embolization of surgically created aneurysms in canines, which respond to coil embolization in a manner similar to humans and thus provide a more clinically relevant in vivo aneurysm model. 4 The PPODA-QT was used to embolize lateral wall aneurysms created in the carotid arteries of canines, which survived for a period of 6 months.…”
mentioning
confidence: 99%
“…Aneurysms were surgically created in the right common carotid artery of adult Yorkshire swine (ϳ130 lb) as previously described (3). A lateral wall carotid artery aneurysm was created by making a 10-cm incision on the right side of the animal's neck to access the right common carotid artery and external jugular vein (EJV).…”
Section: Surgical and Endovascular Proceduresmentioning
confidence: 99%